Association between weekend catch-up sleep and gallstone disease in US adults: a cross-sectional study from NHANES 2017–2020 - Jianwei Cao; Weishuai Zhang; Jixuan Yi; Yang Zhang; Xiaoyan Tong; Xiangnan Zhu (Frontiers in Public Health)
BackgroundGallstones are the most prevalent cause of hospitalization among digestive disorders. For humans, sleep is an essential physiological function. The relationship between gallstones and sleep is well established, but the consequences of weekend catch-up sleep (WCS) on gallstones remain unclear. This research examined the connection between gallstone disease and WCS.MethodsWe included 6,957 participants from the 2017–2020 National Health and Nutrition Examination Survey (NHANES) who met the eligibility criteria and had complete data. Logistic regression, restricted cubic spline, and subgroup analyses were employed to assess the relationship between the presence of gallstones and WCS.ResultsOur study indicated that trouble sleeping and late sleep were risk factors for gallstones in a model adjusted for all covariates. The restricted cubic spline results revealed that WCS was negatively correlated linearly with gallstone disease. Additionally, subgroup analysis showed a statistically significant relationship between WCS > 2 hours and a lower risk of gallstones, particularly among non-smokers and males.ConclusionOur study results demonstrate that trouble sleeping and late sleep increase the incidence of gallstones. In addition, the protective effect of WCS > 2 hours on reducing the incidence of gallstones is particularly significant in individuals who are non-smokers and males, whereas in the smoking population, WCS < 0 hours serves as a protective factor against gallstones.